Interactive Therapeutic System for Children with Autistic Spectrum Disorder (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
This project focuses on children with autism (scientifically called Autism Spectrum Disorder - ASD). It presents an interactive system whose main objective is to help the development of social and motor skills through the accompaniment of the Bioloid robot in humanoid configuration, which is programmed to interact with training routines oriented to physical activity, communication, and socialization.